PENGATURAN KEKAYAAN YAYASAN DITINJAU DARI PASAL 6 UNDANG-UNDANG NOMOR 16 TAHUN 2001 TENTANG YAYASAN - Brahmantya, Ida Bagus Bayu (Kerta Dyatmika, 2023)
Article 6 of Law Number 16 of 2001 concerning Foundations stipulates that “a foundation is obliged to pay all costs or expenses incurred by its organs in the course of performing the foundation’s duties.” However, this provision is open to multiple interpretations, particularly with respect to the terms “costs” and “expenses,” which lack a clear and detailed definition within the statute. The purpose of this study is to analyze the legal framework governing the assets of foundations under Indonesian foundation law and to examine the foundation’s obligation to cover any costs or expenses incurred by its organs namely the Board of Supervisors, the Board of Management, and the Board of Trustees while executing their official duties. This research adopts a normative juridical approach. The findings reveal that the management and regulation of foundation assets are governed by Law Number 16 of 2001 on Foundations, as amended by Law Number 28 of 2004. According to these legal provisions, the assets of a foundation may originate from the founder’s separated wealth, donations, grants, endowments, testamentary gifts, and other legitimate sources. These assets are to be managed in accordance with the authorities and responsibilities of the foundation’s governing organs. While the foundation's obligation to bear operational costs incurred by its organs is clearly stated in Article 6, the legislation does not provide a specific enumeration or categorization of the types of costs or expenses covered. This lack of clarity gives rise to a vague legal norm, which may lead to legal uncertainty and diverse interpretations in practice. Conclusion is although the regulation of foundation assets and the obligation to cover costs incurred by foundation organs are explicitly provided for under Indonesian foundation law, the absence of detailed normative guidance regarding what constitutes reimbursable “costs or expenses” creates interpretive ambiguities and potential legal uncertainty.